Unveiling the Role of Dynamic Alternative Splicing Modulation After Infestation with Sea Lice (Caligus Rogercresseyi) in Atlantic Salmon - Vidal-Soto, R (Springer, 2023)
Sea lice are pathogenic marine ectoparasite copepods that represent a severe risk to the worldwide salmon industry. Several transcriptomic investigations have characterized the regulation of gene expression response of Atlantic salmon to sea lice infestation. These studies have focused on the levels of transcript, overlooking the potentially relevant role of alternative splicing (AS), which corresponds to an essential control mechanism of gene expression through RNA processing. In the present study, we performed a genome-wide bioinformatics characterization of differential AS event dynamics in control and infested C. rogercresseyi Atlantic salmon and in resistant and susceptible phenotypes. We identified a significant rise of alternative splicing events and AS genes after infestation and 176 differential alternative splicing events (DASE) from 133 genes. In addition, a higher number of DASE and AS genes were observed among resistant and susceptible phenotypes. Functional annotation of AS genes shows several terms and pathways associated with behavior, RNA splicing, immune response, and RNA binding. Furthermore, three protein-coding genes were identified undergoing differential transcript usage events, among resistant and susceptible phenotypes. Our findings support AS performing a relevant regulatory role in the response of salmonids to sea lice infestation. © 2023, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.